Multilevel Analysis of the Biopsychosocial Determinants and Contextual Peer Groups on Smoking Habit in High School Students in East Lampung, Lampung, Indonesia - Retno Sulistyani; Setyo Sri Rahardjo; Pawito Pawito (Journal of Health Promotion and Behavior, 2021)
Background: Smoking is still one of the greatest public health threats faced by citizens of the world. Data from the Central Statistics Agency in 2018 shows that smoking behavior in Lampung Province has a prevalence of 35.95%. The World Health Organization (WHO) states that smoking kills more than 8 million people per year worldwide. This study aimed to analyze the determinants of adolescent smoking behavior at the individual level and at the school level.Subjects and Method: This was a cross sectional study conducted in East Lampung Regency, Indonesia, from October to November 2020. A number of 200 male adolescents were selected by random sampling. The dependent variable was smoking behavior. The  independent variables were the influence of parents, peers, media exposure, pocket money, cigarette price, intention, attitude, and contextual effect of school. The data were collected by questionnaire and analyzed using a multiple multilevel logistic regression with Stata 13.Results: The influence of family (b=2.88; 95% CI= 0.73 to 3.85; p= 0.004), peers (b= 2.85; 95% CI= 0.65 to 3.52; p= 0.004), media exposure (b= 3.04; 95% CI= 0.78 to 3.62; p= 0.002), money pocket (b= 3.22; 95% CI= 0.87 to 3.59; p= 0.001), cigarette price (b= 2.73; 95% CI= 0.54 to 3.28; p= 0.006), intention to smoke (b= 2.80; 95% CI= 0.69 to 3.95; p= 0.005), attitude toward smoking (b=3.83; 95% CI= 1.80 to 5.58; p<0.001) increased the likelihood to smoke in male adolescents. School had strong contextual effect on smoking in adolescents with ICC= 21.83%.Conclusion: The influence of family, peers, media exposure, money pocket, cigarette price, intention to smoke, attitude toward smoking increase the likelihood to smoke in male adolescents. School has strong contextual effect on smoking in adolescentsKeywords: smoking behavior, adolescents, contextual effect of schoolCorrespondence: Retno Sulistiani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: retnosulistiani91@gmail.com. Mobile: +6285867006699.Journal of Health Promotion and Behavior (2021), 06(01): 9-20https://doi.org/10.26911/thejhpb.2021.06.01.02